Black Silicon Photovoltaics. Issue 2 (17th December 2014) - Otto, Martin; Algasinger, Michael; Branz, Howard; Gesemann, Benjamin; Gimpel, Thomas; Füchsel, Kevin; Käsebier, Thomas; Kontermann, Stefan; Koynov, Svetoslav; Li, Xiaopeng; Naumann, Volker; Oh, Jihun; et al.
<x xml:space="preserve">Abstract</x> This article presents an overview of the fabrication methods of black silicon, their resulting morphologies, and a quantitative comparison of their optoelectronic properties. To perform this quantitative comparison, different groups working on black silicon solar cells have cooperated for this study. The optical absorption and the minority carrier lifetime are used as benchmark parameters. The differences in the fabrication processes plasma etching, chemical etching, or laser processing are discussed and compared with numerical models. Guidelines to optimize the relevant physical parameters, such as the correlation length, optimal height of the nanostructures, and the surface defect densities for optoelectronic applications are given.